Clinical dermatology and COVID-19 pandemic: Narrative review - Dillon Mintoff; Manas Chatterjee; Indrashis Podder; Alexa Shipman; Anupam Das (Indian Journal of Dermatology, 2021)
The coronavirus disease of 2019 (COVID-19) pandemic has radical repercussions on every aspect of medical science, including dermatology. The magnitude of the impact on clinical dermatology cannot be overemphasized. Dermatologists have been forced to modify and reconsider the way they consult patients. Teledermatology has come up in a big way, with most of the clinicians resorting to technology and software-based consultations. Management of different dermatological conditions like papulosquamous disorders, vesiculobullous disorders, malignancies, etc., needs to be modified as per the different recommendations proposed by expert panels. This review is an attempt to highlight the impact of this destructive pandemic on various aspects of clinical dermatology.